2008
DOI: 10.1002/jmv.21118
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of human herpes virus 6 genome in children with acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia is the main type of leukemia in children. An infectious etiology has been suspected and the role of the Human herpesvirus-6 (HHV-6) has been suggested. Several studies have tried to establish a link between HHV-6 infections and hematological malignancies, with discordant results. The potential role of HHV-6 in the pathogenesis of pediatric acute lymphoblastic leukemia was investigated. HHV-6 genome copy number was measured by quantitative real-time PCR (RQ-PCR) in bone marrow or pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
4
16
1
1
Order By: Relevance
“…In the bone marrow samples at diagnosis, the current results are in accordance with previous findings obtained by Seror et al who detected HHV-6 in 17% of bone marrow samples with a viral load at 23 copies/million cells [14]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the bone marrow samples at diagnosis, the current results are in accordance with previous findings obtained by Seror et al who detected HHV-6 in 17% of bone marrow samples with a viral load at 23 copies/million cells [14]. …”
Section: Discussionsupporting
confidence: 92%
“…[14], but differs from those obtained by Hermouet et al who identified 89% of HHV-6A species, and 11% of HHV-6B [12]. This may be linked to the high number of children included in our study, the frequent occurrence of HHV-6 infections during childhood and to inter-laboratory technical discrepancies.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Eight carried HHV-6B and 1 HHV-6A (one could not be not determined). The detection of low HHV-6 viral loads in a small proportion of ALL patients has been observed previously [40], [41]. Of these 11 samples, one (P451) had a HHV-6 copy number consistent with ciHHV-6.…”
Section: Resultssupporting
confidence: 59%